Reading Proverbs 10–22 - Clifford, Richard J. (Interpretation, 2009)
The proverbs of chs. 10–22 invite ethical reflection not only because they are designed to do so, but also because they are so different from the proverbs we are used to. Chapters 1-9 set chs. 10–22 in the context of building our life according to God's wisdom. Each proverb shows us a facet of human action and divine sovereignty.